Study on preparation of chickpea peptide and its effect on blood glucose - Ma, Xuemei; Fan, Xing; Wang, Deping; Li, Xianai; Wang, Xiaoyun; Yang, Jiangyong; Qiu, Chenggong; Liu, Xiaolu; Pang, Guangxian; Abra, Redili; Wang, Liang (Frontiers in Nutrition, 2022)
Chickpeas are the third largest bean in the world and are rich in protein. In this study, chickpea peptides were prepared by the enzyme-bacteria synergy method. Taking the peptide yield as the index, we first screened 8 strains suitable for the fermentation of chickpea peptides from 16 strains, carried out sodium dodecyl sulfate polyacrylamide gel electrophoresis, and then screened 4 strains with the best decomposition effect of chickpea protein. The molecular weight, amino acid content, and α-glucosidase inhibitory activity of the chickpea peptides fermented by these four strains were detected. Finally, the strains with the best α-glucosidase inhibitory activity were obtained, and the inhibitory activities of the different molecular weight components of the chickpea peptides fermented by the strains with the best α-glucosidase inhibitory were detected. It was found that Bifidobacterium species had the best fermentation effect, and the highest peptide yield was 52.99 ± 0.88%. Lactobacillus thermophilus had the worst fermentation effect, and the highest peptide yield was 43.22 ± 0.47%. Sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE) showed that Bifidobacterium species, Lactobacillus acidophilus, Lactobacillus rhamnosus, and Lactobacillus paracasei have a better effect on the decomposition of chickpea protein in the fermentation process, and the molecular weight of their fermented peptides is basically below 20 KDa. Among the four strains, the α-glycosidase inhibition of chickpea peptide fermented by Lactobacillus acidophilus was the best, which was 58.22 ± 1.10% when the peptide concentration was 5.0 mg/ml. In chickpea peptide fermented by Lactobacillus acidophilus, the influence of molecular weight on the inhibitory activity is not obvious when the molecular weight is <10 kD, and the molecular weight range of the best inhibitory effect is 3–10 kD, and the inhibitory rate of α-glucosidase is 37 ± 1.32% at 2.0 mg/ml. This study provides a theoretical basis for the study of a new preparation method for chickpea peptide and its hypoglycemic effect.